(untitled) (Research, Society and Development, 2020)
This article aims to point out and discuss the representation and social significance attributed to the last phase of human development, namely old age, to revise its concepts based on the thought of Viktor Frankl under the theoretical bias of Logotherapy and Existential Analysis, punctuating and problematizing the ethics that govern contemporary society, based on the will to meaning that is the motivational action of existence. The theoretical foundations of Logotherapy and Frankl’s existential analysis were used in this work, through bibliographic survey, seeking contributions to the theme of this article. For mental health of the elderly it is crucial not to stop living what Frankl suggests that the person never is, but always becomes. A being that is never finished, but while he is living, he has a task or a mission to be accomplished, until the last breath. Live with courage every moment of life.